Mythic journeys [videorecording (DVD)] - Boe, Steven; Boe, Whitney; Curry, Tim; Hamill, Mark; Henriksen, Lance, 1940-; Adler, Charlie, 1956-; Chopra, Deepak; Somé, Sobonfu; Meade, Michael, 1944-; Beckwith, Michael Bernard; Salas, Armando (Cinematographer); Balcomb, Stuart, 1951-; et al. (Alive Mind ; Distributed by Lorber HT Digital, 2010)
Despite the fact that myth has always existed, surprisingly few people today are aware of even the classic myths or the potential myths have to impact their lives. Myths are the reservoir of human wisdom - the story and the meaning of life. Every human being has asked the questions who am I, what is my purpose, why am I here? The answers are in the myths that have been passed on from generation to generation.